2015
DOI: 10.1002/pd.4597
|View full text |Cite
|
Sign up to set email alerts
|

First trimester screening for Down syndrome using nuchal translucency, maternal serum pregnancy‐associated plasma protein A, free‐β human chorionic gonadotrophin, placental growth factor, and α‐fetoprotein

Abstract: The performance of FTS can be enhanced by adding PlGF and AFP. Even without nuchal translucency, the test would perform well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 48 publications
1
24
0
1
Order By: Relevance
“…First trimester maternal serum free β‐hCG levels in OSB have been reported to be reduced in two series, and a published model found that adding both AFP and free β‐hCG to BPD MoM based on CRL increased detection from 50% to 58% for a 5% false‐positive rate . When screening for Down's syndrome in the first trimester, performance can be enhanced by the addition of maternal serum AFP, with or without PlGF . Centres using such protocols will be able to take advantage of the AFP measurement to achieve improved OSB detection.…”
Section: Discussionmentioning
confidence: 99%
“…First trimester maternal serum free β‐hCG levels in OSB have been reported to be reduced in two series, and a published model found that adding both AFP and free β‐hCG to BPD MoM based on CRL increased detection from 50% to 58% for a 5% false‐positive rate . When screening for Down's syndrome in the first trimester, performance can be enhanced by the addition of maternal serum AFP, with or without PlGF . Centres using such protocols will be able to take advantage of the AFP measurement to achieve improved OSB detection.…”
Section: Discussionmentioning
confidence: 99%
“…Predicted performance is based on published statistical parameters for NT, pregnancy‐associated plasma protein‐A (PAPPA), freeβ, and human chorionic gonadotrophin (hCG), NB, TR and DV, NF, NBL, and PT, and ANOMALY; meta‐analysis for placental growth factor (PlGF) and alpha fetoprotein (AFP) based on publications cited in Ref. ; and a standardized maternal age distribution . Rates are based on prevalence at birth.…”
Section: General Considerations For Cfdna Screeningmentioning
confidence: 99%
“…Centers currently using a version of the combined test enhanced by the addition of nasal bone determination will have higher marginal costs when changing protocol because the detection rate advantage of cfDNA testing is smaller. Those currently using a version of the combined test enhanced by additional maternal serum markers, placental growth factor and AFP will need fewer additional funds but will have higher marginal costs.…”
Section: Model‐predicted Proportion Of Down‐syndrome Cases Detected Amentioning
confidence: 99%